The Resilience of al-Shabaab - Anzalone, Christopher
In the face of major territorial, military, and economic setbacks, the Somali insurgent-jihadi group al-Shabaab has proven remarkably resilient thanks to pragmatic decision-making and skilled tactical maneuvering. With strong interpersonal ties and a capable internal security network, the group s senior leadership continues to maintain overall unity and to ward of a strong challenge from Islamic State sympathizers. Despite its transnational rhetoric and afliation with al-Qa`ida, al-Shabaab remains rooted in domestic Somali issues and clan politics. This domestic focus has contributed to a pragmatic battlefield strategy of classic guerilla warfare interspersed with high-profile, well-coordinated attacks on soft targets, such as hotels and restaurants, in the Somali capital of Mogadishu.
Keywords: Al-Shabaab; Resiliencia